TANTANGAN DAN PELUANG MERDEKA BELAJAR: STRATEGI MEMBANGUN KEMANDIRIAN PENDIDIKAN UNTUK MASA DEPAN BERKUALITAS - Natalia, Klara; Surti Ola, Maria Ratnawati; Suswandari, Meidawati (Jurnal Dikdas Bantara, 2023)
Abstract This article discusses the challenges and opportunities in the context of independent learning, with a focus on strategies for developing educational independence to achieve a quality future. The writing method is literature and content analysis from various academic sources that are relevant to the theme of independent learning and educational independence. These challenges involve paradigm shifts, adaptation to technology, and increased community involvement. In addition, this article also identifies opportunities that can be taken to improve the quality of education, such as the use of technological innovation, responsive curriculum development, and strengthening collaboration between education stakeholders. The strategies proposed in this paper aim to form individuals who are able to take an active role in the learning process, while preparing them to face future demands. Therefore, this paper provides an important contribution to thinking about how to create a learning environment that is empowering, independent, and oriented towards quality results. The results of this paper highlight a number of significant challenges in the transformation of the education system, including a paradigm shift towards a more autonomous learning approach, adaptation to advances in learning technology, and increasing community participation in the educational process.